2019
DOI: 10.23937/2643-4466/1710018
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Most Common Dermatologic Conditions and their Debilitating Psychosocial Impacts

Abstract: The majority of skin conditions are not life-threatening; however, many can be severe and disfiguring enough to devastate a patient's quality of life. Skin diseases can significantly impact not only a patient's physical appearance, but also their social and emotional well-being. Even the smallest skin lesions have been shown to disrupt a person's level of overall wellness. Here, we aim to address the potential psychological and emotional impact of the most common and debilitating dermatologic conditions. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 128 publications
0
10
0
Order By: Relevance
“…Dermatological drug products are used to treat skin diseases such as psoriasis, acne, atopic dermatitis, and infections [1]. Development and assessment of local bioavailability of such products face significant challenges as the active pharmaceutical ingredients (APIs) from these drug products reach the site of action (skin layers) before they enter systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermatological drug products are used to treat skin diseases such as psoriasis, acne, atopic dermatitis, and infections [1]. Development and assessment of local bioavailability of such products face significant challenges as the active pharmaceutical ingredients (APIs) from these drug products reach the site of action (skin layers) before they enter systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The aims of the work presented here were to use this dermal PBPK model to [11] predict clinically observed concentration-time profiles of clobetasol-17 propionate (CP) formulated in Dermovate TM cream, 0.05% obtained using the dOFM technique. (1); and [1] correlate local dermis exposure with Dermovate TM cream, 0.05% (GlaxoSmithKline Pharma, GmBH, Vienna, Austria) formulation properties. This product was identified as a case study based on the availability of clinical dermal CP concentration-time profiles using the dOFM technique to examine skin permeation.…”
Section: Introductionmentioning
confidence: 99%
“…Pruritus and scratching can lead to pain, bleeding and sleep disturbance. Other studies have demonstrated that sleep disturbances resulting from atopic dermatitis also carry a psychosocial burden reflected by drowsiness, inability to focus, irritability, and growth restriction (4). Impacts on physical functioning include clothing restrictions, interference with indoor and outdoor activities such as bathing and swimming, and embarrassment (5).…”
Section: Consequences Of Ad In Childrenmentioning
confidence: 99%
“…Androgenetic alopecia (AGA) is a common disorder affecting more than half of adults worldwide with marked psychosocial impacts on affected individuals [1]. With the underlying pathophysiology still poorly understood, there have been extensive efforts to devise modern and more effective treatment modalities in recent times.…”
Section: Introductionmentioning
confidence: 99%